2014
DOI: 10.1097/wno.0000000000000093
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Episodes of Perioperative Ischemic Optic Neuropathy After Hip Surgery

Abstract: Perioperative ischemic optic neuropathy (ION) after nonocular surgery is a rare complication leading to permanent and often severe vision loss. Due in part to the low prevalence of this complication, there remains no reliable way to predict which patients will develop ION. We present a patient with sequential episodes of unilateral perioperative ION, both occurring after otherwise uncomplicated hip operations. Patients and physicians should be aware that perioperative ION after one surgery may increase the ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…23 Patients and physicians should be aware that perioperative ION after one surgery may increase the chance of ION after subsequent surgeries. 23…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…23 Patients and physicians should be aware that perioperative ION after one surgery may increase the chance of ION after subsequent surgeries. 23…”
Section: Discussionmentioning
confidence: 99%
“…One study reported sequential episodes of right AION following uncomplicated hip operations performed in the lateral decubitus position. 23 Patients and physicians should be aware that perioperative ION after one surgery may increase the chance of ION after subsequent surgeries. 23 Central retinal artery occlusion is a commonly reported cause of postoperative blindness that generally manifests unilaterally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations